Phytochemical profiling and in vitro biological activity evaluation of Lavandula angustifolia flower essential oil - Mohan Lal; Raghu Tamang; Priyanka Dutta; Twahira Begum; Mansour Ghorbanpour (Scientific Reports)
Abstract Lavandula angustifolia is an economically important plant containing essential oil. In the present study, the chemical composition, biological activities and genotoxicity of Lavendula angustifolia flower essential oil (LAFEO) were investigated. The essential oil was extracted using a Clevenger-type apparatus and subsequently analyzed for its biological activities. LAFEO chemical analysis revealed major compounds like linalyl acetate, linalool, lavandulyl acetate, linderol, eucalyptol, caryophyllene and caryophyllene oxide with area 51.06 29.71, 3.34 2.25, 2.19 1.19, 1.16% respectively. The ABTS and DPPH assay of LAFEO showed an IC50 value of 7.18 and 8.25 µL/ml respectively. The trypsin inhibitory assay showed similar results with the standard sodium diclofenac with an IC50 value of 3.00 µL/mL for LAFEO and 3.55 µL/mL for sodium diclofenac. acetylcholinesterase inhibitory (AChE) activity of LAFEO showed strong AChE potential (IC50 = 3.66 µL/mL) compared to galanthamine (IC50 = 4.32 µL/mL) which explains that L. angustifolia can be strong candidate for the drug formulation of Alzimer related disorders. In tyrosinase inhibitory activity, LAFEO showed IC50 value of 1.89 µL/mL whereas kojic acid with 2.47 µL/mL. In antidiabetic activity, the LAFEO showed strong activity (IC50 = 1.91 µL/mL) compared to acarbose (IC50 = 2.10 µL/mL). From the current study, it can be concluded that LALEO shows strong acetylcholinesterase inhibitory activity, suggesting its potential use in treating memory-related disorders after validation. Additionally, it may serve as a natural candidate for developing anti-diabetic, antioxidant, skin-whitening, and anti-inflammatory drugs in the near future with more in vivo validation.